2023
DOI: 10.1080/22221751.2023.2172965
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of the newly emerged H7N9 avian influenza viruses

Abstract: Since the first human case in 2013, H7N9 avian influenza viruses (AIVs) have caused more than 1500 human infections with a mortality rate of approximately 40%. Despite large-scale poultry vaccination regimes across China, the H7N9 AIVs continue to persist and evolve rapidly in poultry. Recently, several strains of H7N9 AIVs have been isolated and shown the ability to escape vaccine-induced immunity. To assess the zoonotic risk of the recent H7N9 AIV isolates, we rescued viruses with hemagglutinin (HA) and neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Influenza HA proteins, in particular the globular head domain, are highly variable, and the COBRA methodology was used to generate vaccine candidates capable of covering multiple epitopes to address the antigenic diversity and to preserve the conserved epitopes to elicit protection against previous and future strains. Influenza H7N9 viruses infected more than 1500 people in 2013-2017 and caused a mortality rate of an approximately 40% [12]. They are still circulating in animal reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza HA proteins, in particular the globular head domain, are highly variable, and the COBRA methodology was used to generate vaccine candidates capable of covering multiple epitopes to address the antigenic diversity and to preserve the conserved epitopes to elicit protection against previous and future strains. Influenza H7N9 viruses infected more than 1500 people in 2013-2017 and caused a mortality rate of an approximately 40% [12]. They are still circulating in animal reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike seasonal influenza viruses among humans, sporadic human infections with the avian influenza viruses (AIVs) H5N1 and H7N9 can lead to more severe disease outcomes and higher mortality rates than any other subtypes of influenza virus [8][9][10]. The first case of H7N9 AIV in humans was reported in 2013 [11], and more than 1500 people became infected and ~40% of these infections resulted in death [12]. In addition, the infection of domestic poultry with H7 influenza viruses results in dramatic economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that H9N2 viruses can contribute internal genes to other subtypes of AIV. For instance, the novel reassortant H7N9 virus, which emerged in 2013, contains all six internal genes derived from the H9N2 virus ( Lam et al., 2013 ; Liu et al., 2013 ) and has caused over 1500 human infections with a fatality rate of approximately 40% as of January 13, 2023 ( Chang et al., 2023 ). The H10N8 virus, which has caused human infection and death, also has six internal genes derived from H9N2 ( Chen et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The H9N2 AIV pandemic in 1999 caused significant economic losses in the poultry industry (Cao et al, 2022). The H7N9 AI pandemic in 2013 ranged in shape and had a lipid envelope containing two surface glycoproteins, HA, and NA (Chang et al, 2023). The AIV genome has eight segments, and these segments encode 11 viral proteins (Suarez & Schultz, 2000).…”
Section: Introductionmentioning
confidence: 99%